2019
DOI: 10.3390/ma12030482
|View full text |Cite
|
Sign up to set email alerts
|

Shape-Memory Assisted Scratch-Healing of Transparent Thiol-Ene Coatings

Abstract: A photopolymerizable thiol-ene composition was prepared as a mixture of pentaerythritol tetrakis(3-mercaptopropionate) (PETMP) and 1,3,5-triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione (TTT), with 1 wt. % of 2,2-dimethoxy-2-phenylacetophenone (DMPA) photoinitiator. A systematic analytical analysis that investigated the crosslinked PETMP-TTT polymer coatings employed Fourier transform infrared spectroscopy, ultraviolet–visible spectroscopy, differential scanning calorimetry, thermogravimetric analysis, pencil ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
18
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 41 publications
2
18
0
Order By: Relevance
“…Heat treatment for recovery process of the deformed PETMP-TTT films was performed in an oven at 100 • C (i.e., recovery temperature) for 1 h under an air atmosphere. It is worth mentioning that glass transition temperature (T g ) for the particular thiol-ene composition is 41 ± 1 • C, as reported in our previous work [26]. The glassy transition is the primary mechanism that governs the shape-memory behavior of PETMP-TTT film.…”
Section: Mechanical Deformation and Recoverysupporting
confidence: 67%
See 2 more Smart Citations
“…Heat treatment for recovery process of the deformed PETMP-TTT films was performed in an oven at 100 • C (i.e., recovery temperature) for 1 h under an air atmosphere. It is worth mentioning that glass transition temperature (T g ) for the particular thiol-ene composition is 41 ± 1 • C, as reported in our previous work [26]. The glassy transition is the primary mechanism that governs the shape-memory behavior of PETMP-TTT film.…”
Section: Mechanical Deformation and Recoverysupporting
confidence: 67%
“…Photopolymerizable thiol-ene composition was prepared as reported previously [26]. A photoinitiator was briefly dissolved in a warm PETMP at 60 • C in an amber glass jar, then the calculated amount of TTT was added, avoiding direct day or artificial light.…”
Section: Preparation Of the Thiol-ene Composition Casting And Uv Polmentioning
confidence: 99%
See 1 more Smart Citation
“…Thiol-ene polymer systems are of particular interest as they present numerous advantages including fast polymerization, low volume shrinkage, homogeneity of the polymer network, flexibility and high optical transparency of the polymerized films [ 32 , 33 ]. It was reported that thiol-ene polymer networks exhibit a good shape recovery and self-healing effect [ 34 ]. Recently, our group demonstrated an efficient recovery of microstructured thiol-ene films fabricated via casting and a UV polymerization technique on silicon substrates textured using electron beam lithography [ 35 ].…”
Section: Introductionmentioning
confidence: 99%
“…Over the past two decades, the versatility of thiol–ene click chemistry has been greatly exploited in polymer and materials science 25–29. The ability to combine thiol–ene chemistry with other functionalization reactions and polymerization techniques allows enhanced control and specificity in macromolecular architectures, providing the access to multifunctional materials (e.g., block copolymers,30 dendrimers,31 biomaterials,32 cross‐linked materials,33 and colloidal nanoparticles34,35). The thiol–ene crosslinking of multifunctional thiols with nonactivated CC double bonds is currently utilized in surface coating due to many advantages (e.g., regioselectivity, quantitative yields, facile synthetic strategies, and tolerance to many solvents or reaction conditions) over other synthetic methods, especially those employing heavy‐metal catalysts 31,36–39.…”
mentioning
confidence: 99%